2010
DOI: 10.1016/j.jmwh.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Pregnancy: Women's Perceptions, Practices, and Influencing Factors

Abstract: To facilitate women's self-management across these phases, support is needed that focuses on providing strategies to strengthen individual approaches by women. Such support might promote activities of daily living as a specific entity of physical activity, expose myths about activity during pregnancy, and endorse the benefits of weight management arising from physical activity, not just during pregnancy, but across the lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
83
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 31 publications
12
83
0
6
Order By: Relevance
“…The retrospective studies included 2 cross sectional studies asking for retrospective recollections of physical activity (Cioffi et al, 2010;Haakstad et al, 2007), 2 retrospective recall questions in cohort studies (Symons-Downs and Hausenblas, 2004;Waellens et al, 2003) and 1 secondary analysis (Mottola and Campbell, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The retrospective studies included 2 cross sectional studies asking for retrospective recollections of physical activity (Cioffi et al, 2010;Haakstad et al, 2007), 2 retrospective recall questions in cohort studies (Symons-Downs and Hausenblas, 2004;Waellens et al, 2003) and 1 secondary analysis (Mottola and Campbell, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The physical activity goalsetting tool emphasized improving awareness about the safety of exercise during pregnancy because previous research found it to be a barrier to physical activity during pregnancy. [20][21][22] In addition, the tool focused on assessing barriers to being active and identifying strategies specific to those barriers. Below are the steps that were part of the physical activity goal-setting feature:…”
Section: Aim 2: the E-moms Roc Intervention And Its Implementationmentioning
confidence: 99%
“…The schedule contained questions on physical activity, healthy eating, gestational weight gain; and sources of health information. The questions were devised after a comprehensive review of the literature (24,(35)(36)(37)(38)(39) , reviewed by physical activity and nutrition experts and pilot tested. (See Appendix A for example questions).…”
Section: Interview Schedulementioning
confidence: 99%